The effect on self-efficacy on the level of physical activity in adolescents of the Driyorejo Health Center Area, Gresik Regency - Afina Puspita Zari (Journal of Midwifery and Nursing, 2026)
Obesity has become a complex issue that can affect all age groups, including adolescents. One of the primary causes of obesity is a lack of physical activity. Low levels of physical activity among adolescents are influenced by various factors, including individual factors such as sex and age. Additionally, low self-efficacy in engaging in physical activity plays a significant role. This study aims to analyse the impact of self-efficacy on the level of physical activity among students. This study employed a quantitative approach with an observational research type. The research was conducted utilising a cross-sectional design. The study was carried out in four high schools within the Driyorejo Community Health Centre area, involving a total of 335 students. The sampling method employed was proportionate stratified random sampling. The research took place from March to April 2024. The data analysis was performed using SPSS version 25 with ordinal logistic regression analysis. The results of the multiple ordinal regression analysis for physical activity suggested that sex (p=0.000) and self-efficacy (p=0.000) had p-values less than 0.05, indicating a significant effect of both sex and self-efficacy on the level of physical activity among students in the Driyorejo Community Health Centre area. Therefore, efforts that can be undertaken include optimising the role of the School Health Unit (UKS) to provide opportunities for adolescents to share experiences within peer groups, thereby enhancing their motivation to engage in physical activity.